Constraints and strategies for the management of conflicts in Africa (2008)
The end of the Cold War instigated a new approach into the operation of world politics, with the promotion of peace and security\ This assumption is however different n the continent of Africa, because conflicts in this period have been volatile and protracted’ While some scholars analysed causes of conflict in Africa as a result of internal wranglings, other viewed it from the standpoint of modernization: In spite of these divergent opinions, conflicts in Africa did not only destabilize the operation of the political system but also make sustainable development a difficult task. The discursion starts with the analysis of the nature, causes and consequences of the conflict. In response to the negative consequences of such conflicts, this paper examines the constraints to the management of conflict in Africa and suggests the relevant strategies to employ in managing the conflicts. The paper concludes that for any meaningful peace and sustainable development to be attained in Africa, nation-building, justice and good governance should be brought to the center stage of continental politics and international relations